Catalogue of LPS-induced transcriptional changes across vertebrates identifies syntenically conserved human long non-coding RNAs that regulate the innate immune response - Hadjicharalambous, Marina R.; Ryder, Richard R.; Fenwick, Peter S.; Donnelly, Louise E.; Lindsay, Mark A. (Frontiers in Immunology, 2026)
BackgroundInnate immunity involves the detection and removal of pathogens and is an ancient physiological response observed across all living organisms. Long non-coding RNAs (lncRNAs) are a novel family of RNA transcripts that regulate the innate immune response. Although the identification of functional lncRNAs has been hindered by their poor evolutionary sequence conservation, it has been speculated that syntenic conservation (position relative to protein coding genes) might provide an alternative approach. To examine this hypothesis, we have produced a catalogue containing the LPS-induced transcriptional changes across 27 vertebrate species, which was employed to identify syntenically conserved and functional LPS-induced human lncRNAs.MethodsTranscriptomics was employed to compare differential lncRNA expression, as well as mRNA expression, between LPS-stimulated human cells and 26 vertebrate species, including 7 primates, 10 mammals, 4 birds and 5 fish. The function of manually annotated syntenically conserved human lncRNAs was examined in LPS-stimulated monocytic THP-1 cells using antisense mediated knockdown.ResultsSequencing data from 9 LPS-stimulated human cell studies was analysed to produce a high confidence catalogue of 1036 mRNAs and 71 lncRNAs that were differentially expressed in 4 or more cell types. Examination of the mRNAs involved in the LPS signaling pathway showed evolutionary conservation across human, primates, mammals, birds and fish, one notable exception being the absence of the LPS sensing complex (MD2/TLR4/CD14) in fish. To overcome poor sequence conservation amongst lncRNAs, we employed syntenic position to show that many of the 71 lncRNAs identified in humans were conserved and induced across vertebrates, the most common being MITA1 (IL7AS) and LINC02541. Knockdown studies showed that MITA1 (IL7AS) and LINC02541 negatively regulate the human LPS-induced inflammatory response in monocytic THP-1 cells. Significantly, we have identified regions/domains of MITA1 (IL7AS) and LINC02541 that are conserved across vertebrates.ConclusionThis report provides a comprehensive catalogue of the transcriptional response following activation of the LPS-induced innate immune response across 9 human cell types and 26 vertebrate species. We show that many of the LPS-induced human lncRNAs are syntenically conserved and induced across vertebrate species and that this can predict a functional role in the human innate immune response.